Preventing Disruptive Behavior in Elementary School Students: An Academic Investigation from a Multicultural Islamic Education Lens - Khoirotun, Ulfun; el yunusi, Muhammad Yusron Maulana (Paedagogia: Jurnal Pendidikan, 2023)
The objective of this study is to identify strategies for enhancing the social development of children within inclusive educational settings. The present study employs a qualitative research design and adopts a phenomenological framework. The study was conducted in SD Muhammadiyah 3, Ikrom Wage Sidoarjo, with a sample size of five individuals who were chosen as participants. The data collection process involved the utilisation of in-depth interviews and observation techniques, which were subsequently followed by data reduction and data display procedures. Subsequently, the data underwent analysis by the method of triangulation. The present study yielded the subsequent findings: The term "character" refers to the attributes, traits, and qualities that define an individual's personality and behaviour. It encompasses a The social attributes of pupils at SD Muhammadiyah 3 Ikrom were enhanced, encompassing virtues such as honesty, civility, social responsibility, tolerance, democracy, and justice. The process of enhancing character development is implemented for all students, especially those who possess exceptional requirements. The implementation of multicultural education is accomplished through two primary methods: firstly, by incorporating it into the curriculum across many disciplines taught in the classroom, and secondly, by fostering a school environment that embraces and upholds the principles and values of multicultural education. The process of integrating subjects is facilitated with the active participation of educators who have received specialised training. Educators receive periodic training sessions focused on strategies and approaches for instructing students with exceptionalities. In the context of educational institutions, the process of school acculturation is often implemented during the initial orientation phase for incoming students. During student orientation, it is crucial to prioritise the instruction of habits and fostering a sense of acceptance towards individuals with diverse backgrounds.